1992
DOI: 10.1007/bf00193840
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effects of jasmonic acid on potato stem node and protoplast culture

Abstract: The effect of jasmonic acid (JA), in a wide range of concentrations (0.01-100 ~M), on the development of potato plantlets (Solanum tuberosum L.cv. Vesna) was investigated in order to discriminate between physiological and supraoptimal effects of this growth regulator in vitro. Concentrations from 0.I-I I~M significantly increased the length of developed plants. Application of JA in these concentrations resulted in a very well differentiated root system with many lateral branches. With increasing JA concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
48
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 15 publications
14
48
1
Order By: Relevance
“…This is especially true with regard to growth inhibition, where both compounds display similar inhibitory activities. In particular, longitudinal growth of potato roots and shoots is inhibited by micromolar concentrations of JA (Ravnikar et al, 1992). Therefore, the inability of JA to suppress sprouting in FLD-treated tubers further strengthens the hypothesis that ABA is not merely acting as a growth inhibitor but rather is restoring dormancy in FLD-treated microtubers.…”
Section: Dlscusslonsupporting
confidence: 52%
“…This is especially true with regard to growth inhibition, where both compounds display similar inhibitory activities. In particular, longitudinal growth of potato roots and shoots is inhibited by micromolar concentrations of JA (Ravnikar et al, 1992). Therefore, the inability of JA to suppress sprouting in FLD-treated tubers further strengthens the hypothesis that ABA is not merely acting as a growth inhibitor but rather is restoring dormancy in FLD-treated microtubers.…”
Section: Dlscusslonsupporting
confidence: 52%
“…Addition of JA resulted in a 5.67-fold increase in shoot length compared to the control. The results of the present experiment are in agreement with those of Ravnikar et al (1992), Martin-Closas and Pelacho (1997), Martin-Closas et al (2000), and Pruski et al (2002), who suggested that JA could play an important role by inducing a general increase in the vegetative development of the in vitro-cultured potato explants. The results of this study show similarities with those of , Dermastia et al (1994), and Dermastia et al (1996).…”
Section: Shoot Lengthsupporting
confidence: 93%
“…showed that meristem growth induction medium supplemented with 0.5 -10 μM JA increased the number of potato meristems, which developed buds without symptoms of senescence. Addition of JA to the growth medium affected the vegetative development of plantlets ) and stimulated root formation of the in vitro cultured potato explants (Ravnikar et al 1992). Zhang et al (2006) showed that the application of 0.2-2.0 mg·dm -3 JA resulted in a significant increase in shoot fresh mass, as well as the number and the root length of plantlets.…”
Section: Introductionmentioning
confidence: 99%
“…RAVNIKAR et al (1992) also observed similar effects in the application of jasmonic acid in potato, and that BAUSHER &YELENOSKY (1986) andBARNES et al (1989) reported restrictions in root development of citrus, soybeans and corn treated with triazoles. Figure 1 shows that in the second week of root sampling, in the treatment with a dose of 800g c.p.…”
Section: Resultsmentioning
confidence: 54%